A questionnaire based study to assess knowledge, attitude and practice of pharmacovigilance among exam going second year undergraduate medical students in a South Indian teaching hospital - N., Umashankar; K. H., Hemanth Kumar; M. S., Kishore (International Journal of Basic & Clinical Pharmacology, 2022)
Background: Pharmacovigilance not only helps in the early detection of adverse drug reactions (ADRs) but also facilitates the identification of both, risk factors and the underlying mechanism. To increase the reporting rate, it is essential to improve the knowledge, attitude, and practices (KAP) of healthcare professionals regarding ADR reporting and pharmacovigilance, especially during undergraduate and postgraduate education. The objective of this study was to assess the KAP about pharmacovigilance among exam-going second-year undergraduate medical students. Methods: A cross-sectional questionnaire-based study was conducted among 150 exam-going second-year undergraduate students from Mysore Medical College and Research Institute, Mysore from April 2022 to June 2022. A validated questionnaire consisting of 22 questions divided into 3 sections; knowledge, attitude, and practice was used. Statistical analysis of data was done using an MS excel spreadsheet. Results: Out of the 150 participants 133 had good knowledge about ADR and pharmacovigilance. Majority of the students agreed that reporting of ADRs is necessary (95.3%), mandatory (95.3%), and should be included in pharmacology practicals (94.7%). Only 29.3% of the students had witnessed an ADR and none of the participants had ever reported an ADR indicating poor practice among the undergraduate students. Conclusions: Students had good knowledge and positive attitude towards ADR reporting and pharmacovigilance. Practice regarding pharmacovigilance was found to be poor, indicating the need for training the undergraduate students in ADR reporting by including ADR recognition and reporting as a part of clinical posting curriculum.